PENGARUH KESADARAN WAJIB PAJAK DAN PENGETAHUAN PERPAJAKAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2021)
The data source used in this study is primary data. Primary data is obtained by using a questionnaire in the form of a structured questionnaire with the aim of collecting information from taxpayers in Tegalangus Village. Sampling in this study was conducted using nonprobability sampling techniques, namely sampling techniques that do not provide equal opportunities / opportunities for each element or member of the population to be selected as samples. Analysis of the data used is the regression analysis, t-test and F-test. Data management with the help of SPSS software (Statistical Product and Service Solution) version 24. Based on the results of the analysis carried out, it was concluded that the awareness of taxpayers, and knowledge of taxation of taxpayers had a positive and significant influence on taxpayer compliance in Tegalangus Village. Keywords : Taxpayer Awareness, Tax Knowledge of Taxpayers, and Taxpayer Compliance.
Keywords: Taxpayer Awareness; Tax Knowledge of Taxpayers; and Taxpayer Compliance.